FILSAFAT ETIKA IBN MISKAWAIH - Hakim, Abdul (Jurnal Ilmu Ushuluddin, 2014)
Ibn Miskawayh is one of the Islamic philosophers who focused on the study of ethics. In his âTahdheeb al-Akhlaqâhe reflects on the concept of ethics systematically using Greek philosophy and combine it with the Qurâan and hadith.Although compared to the concept of ethics of Immanuel Kantâs deontology, ethics Ibn Miskawayh not apply well tothe rule of law. However, the severity of the effort is a big contribution on the development of ethical discourse thatconnects ârational ethicsâ and âethical revelationâ.